Assessing the association of shoulder pain risk with physical fitness in badminton players at national tournament level - Zhou, X.; Imai, K.; Liu, X.; Chen, Z.; Watanabe, E. (Asian Journal of Sports Medicine, 2022)
Background: Shoulder pain which affects sports performance and activities of daily life, is a common musculoskeletal problem experienced by badminton players. Objectives: This study aimed to identify the association of shoulder pain with physical fitness in elite university badminton players participating in the national tournament via medical check-ups. Methods: Physical fitness evaluations were performed among fifty-two 18 - 22 years old university badminton players participating in the national tournament. Handgrip strength, heel buttock distance, angle of straight leg raise, single leg stance, shoulder range of motion, and trunk range of motion were assessed. The prevalence of present shoulder pain was described. Multivariable logistic regression was used to examine the association of present shoulder pain with physical fitness. Results: Sixteen badminton players (30.8%) sustained present shoulder pain related to badminton. Dominant trunk rotation (adjusted OR: 0.91, 95% CI: 0.84 - 0.99, P-value = 0.028) and single leg stance of the nondominant leg (adjusted OR: 0.97, 95% CI: 0.94 - 1.00, P-value = 0.048) were significantly associated with the presence of present shoulder pain. Conclusions: Decreased trunk rotation and deficit in single-leg stance balance might be potential risk factors associated with physical fitness for shoulder pain in university badminton players at national tournament level. These findings can help draw the attention of badminton coaches, players, and team members to facilitate physical fitness promotion for badminton pain/injury prevention.